2017
DOI: 10.1093/eurpub/ckx051
|View full text |Cite
|
Sign up to set email alerts
|

Associations between self-rated health, mental health problems and physical inactivity among urban adolescents

Abstract: Previous research revealed that self-rated health was associated with various mental health problems. Our findings add to these results by showing that physical activity and sedentary behaviour are also very important additional factors related to self-rated health. Better understanding of these associations can help in developing more effective public health intervention programmes for adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
(18 reference statements)
5
28
0
1
Order By: Relevance
“…The detailed results are presented in the Additional files, including the assessments of PA, SB and SRH, statistical methods and confounders adjusted for in the regression, and the key results (see Additional file 3 ). The review included 59 cross-sectional studies and nine longitudinal studies [ 1 4 , 25 28 , 35 94 ]. Most of the studies ( n = 43) were conducted in European countries (e.g., UK, Spain, Finland, Sweden, Norway, Portugal, Hungary) or used data from multiple countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed results are presented in the Additional files, including the assessments of PA, SB and SRH, statistical methods and confounders adjusted for in the regression, and the key results (see Additional file 3 ). The review included 59 cross-sectional studies and nine longitudinal studies [ 1 4 , 25 28 , 35 94 ]. Most of the studies ( n = 43) were conducted in European countries (e.g., UK, Spain, Finland, Sweden, Norway, Portugal, Hungary) or used data from multiple countries.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies observed a dose-response relationship between PA and SRH, where an increasing level or amount of PA was related to a higher odds of “good or excellent” SRH (see Additional file 3 ) [ 1 , 4 , 27 , 41 , 42 , 46 , 48 , 54 , 60 , 68 , 70 , 86 ]. For example, the study by Lachytova et al (2017) found in a sample of adolescents aged 14–16 years old that relative to students who exercised less than once a week, students who exercised every day were 8.04 times more likely to report “good and excellent” health; students who exercised 4–6 times a week and 2–3 times a week were 3.67 times and 1.35 times, respectively, more likely than those exercised less than once a week to have “good and excellent” health after adjusting for gender, BMI, mental health and sedentary behaviour in the logistic regression [ 4 ]. Herman et al (2015) reported that Canadian boys who were moderately active or inactive were 1.59 and 2.09 times, respectively, more likely to report lower health than peers who were physically active [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous health benefits allow considering PA a powerful tool for the prevention of noninfectious chronic disease. On the contrary, physically inactive adolescents tend to have decreased cognition (e.g., academic performance and memory) [4], higher body fat [5], and worse health [6,7] compared to their physically active same-age peers. erefore, in order to identify the reasons for the modification of adolescent PA and to develop measures for the prevention of noninfectious chronic diseases, an objective study of this group, taking into account the peculiarities of lifestyle, is necessary [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on older Croatian adults showed that, among other factors, higher self-rated health in 65-year-olds and over was associated with higher educational level, better health, better functional ability (26), and higher life satisfaction (37). This finding was no surprise, since subjective estimation of one's health comprises broad mental health aspects (38). We should bear in mind, however, that the relation between depression and perception of one's health is bi-directional, as depression contributes to the self-perception of poor health.…”
Section: Mental Health Of Older Croatian Workersmentioning
confidence: 85%